What can academics contribute to the study of financial stability? - Goodhart, Charles A. E. (Economic & Social Studies, 2005)
There were hardly any banking crises between 1939 and 1971, so their later reemergence came as a surprise. Central bank supervisors responded practically by discovering and encouraging the adoption of current best practice in risk management by individual banks, without much theoretical input, whereas economists have mostly focused on models which abstract from default. But default is central to analysis of financial stability. Shubik pioneered introducing default into formal models, and we aim to develop this further. Meanwhile, estimating the probability of default (PD) for individual, or groups of, banks is central to the Basel II process.
This paper was delivered as the Central Bank of Ireland Edgeworth Lecture at the Nineteenth Annual Conference of the Irish Economic Association at Kilkenny, May 7, 2005
Keywords: Financial stability; Risk assessment; Academic research; Financial crises; Bank regulation; Central banks